Transcriptomic analysis shows that surgical treatment is likely to influence the endometrial receptivity of patients with stage III/IV endometriosis - Xiang, Rui; Chen, Peigen; Zeng, Zhi; Liu, Huijun; Zhou, Juan; Zhou, Chuanchuan; Peng, Jintao; Zeng, Haitao (Frontiers in Endocrinology, 2022)
Background Endometriosis negatively affects fertility, and it’s a common disease in assistant reproductive practice. Surgical removal of endometriotic lesions is widely carried out to relieve symptoms and promote fertility. But it’s not intensively investigated what changes in the secretory eutopic endometrium of patients with endometriosis after surgery. Methods Eighteen patients were included in the study, and they were divided into the untreated group and the treated group (6 vs. 12). Basic clinical data was compared, and transcriptomic data of the secretory eutopic endometrium was analyzed with DESeq2, Cytoscape, Cluego, CluePedia, and GSEA. CIBERSORT was used to calculate the relative abundance of 22 immune cells in the samples. Results We determined 346 differentially expressed genes using Deseq2. These DEGs were used to enrich 7 Gene Ontology terms including 3 associated with immune processes and 1 correlated to prostaglandin using Cluego and CluePedia. GSEA enriched 28 Gene Ontology terms in the treated group mainly associated with immune and blood pressure regulation process. Compared to the untreated group, the relative abundance of resting CD4+ memory T cells (0.218 (0.069, 0.334) vs. 0.332 (0.181, 0.429), P = 0.022) and the even less abundant memory B cells (0.001 (0.000, 0.083) vs. 0.033 (0.007, 0.057), P = 0.049) are significantly decreased in the treated group. Conclusion Surgical treatment is likely to influence the endometrial receptivity of patients with endometriosis, but more evidence is needed.